Unfair Business Competition in the E-Commerce Ecosystem: Comparison of Indonesian and South Korean Regulations - Andika Prawira Buana; Firdaus Arifin (Artes Libres Institutum, 2025)
This research provides a comprehensive comparative analysis of the regulatory frameworks for e-commerce in Indonesia and South Korea, focusing on how each country manages unfair business practices within their digital markets. The study employs a normative legal research method, incorporating systematic literature reviews and a comparative approach to explore the intricacies of each country's legal frameworks and their enforcement mechanisms. The findings reveal significant differences in the level of technological integration and the specificity of legal frameworks between the two countries. South Korea exhibits a more advanced regulatory framework with specific e-commerce laws and robust technological enforcement mechanisms that enhance compliance and market monitoring. Conversely, Indonesia's broader and less specific regulations result in ambiguities that hinder effective enforcement and compliance. The study suggests that Indonesia could benefit from refining its legal framework to include more precise regulations tailored to digital transactions and enhancing its technological capabilities for enforcement. This comparative analysis underscores the importance of adaptive and technology-driven regulations in maintaining fair competition and safeguarding consumer interests in the rapidly evolving digital marketplace.